THE EFFECTIVENESS OF THE BLOOKET IN ENHANCING VOCATIONAL HIGH SCHOOL STUDENTS' READING COMPREHENSION ACHIEVEMENT - Mira Maulida Rahmah (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
Low reading comprehension ability among students remains one of the challenges in English language learning, particularly in understanding descriptive texts that involve identifying main ideas, specific information, vocabulary, inference, and referential meaning. This condition indicates the need for innovative and interactive learning media to improve students’ engagement and reading skills. This study aims to analyze the effectiveness of using the Blooket platform in improving students’ reading comprehension achievement in descriptive texts among tenth-grade students of Vocational High School (SMK) majoring in Office Management. This study employed a quasi-experimental approach with a pre-test and post-test control group design. The research participants consisted of tenth-grade vocational school students who were divided into an experimental group taught using Blooket and a control group taught through conventional instruction. The research instrument was a multiple-choice reading comprehension test covering several reading skill aspects. The data were analyzed using statistical tests, including normality tests, homogeneity tests, independent sample t-tests, and effect size analysis. The results indicate that the use of Blooket has a positive effect on improving students’ reading comprehension compared to conventional learning methods. The Blooket platform provides a more interactive and engaging learning environment and increases students’ involvement in understanding descriptive texts. Therefore, Blooket can be used as an effective game-based learning alternative to support the improvement of reading comprehension skills among vocational high school students. ABSTRAK Rendahnya kemampuan pemahaman membaca siswa menjadi salah satu permasalahan dalam pembelajaran bahasa Inggris, terutama dalam memahami teks deskriptif yang mencakup kemampuan mengidentifikasi ide utama, informasi spesifik, kosakata, inferensi, dan makna referensial. Kondisi tersebut menunjukkan perlunya penggunaan media pembelajaran yang inovatif dan interaktif untuk meningkatkan keterlibatan serta kemampuan membaca siswa. Penelitian ini bertujuan untuk menganalisis efektivitas penggunaan platform Blooket dalam meningkatkan prestasi pemahaman membaca siswa pada materi teks deskriptif di kelas X Sekolah Menengah Kejuruan (SMK) jurusan Manajemen Perkantoran. Penelitian ini menggunakan pendekatan kuasi-eksperimen dengan desain pre-test and post-test control group design. Subjek penelitian terdiri atas siswa kelas X SMK yang dibagi menjadi kelompok eksperimen dengan pembelajaran menggunakan Blooket dan kelompok kontrol dengan pembelajaran konvensional. Instrumen penelitian berupa tes pemahaman membaca berbentuk pilihan ganda yang mencakup beberapa aspek kemampuan membaca. Data dianalisis menggunakan uji statistik meliputi uji normalitas, uji homogenitas, uji-t sampel independen, dan analisis ukuran efek (effect size). Hasil penelitian menunjukkan bahwa penggunaan Blooket memberikan pengaruh positif terhadap peningkatan kemampuan pemahaman membaca siswa dibandingkan pembelajaran konvensional. Media Blooket mampu menciptakan pembelajaran yang lebih interaktif, menarik, dan meningkatkan keterlibatan siswa dalam memahami teks deskriptif. Dengan demikian, Blooket dapat digunakan sebagai alternatif media pembelajaran berbasis permainan yang efektif untuk mendukung peningkatan kemampuan pemahaman membaca siswa SMK.